Academic rankings: how should they be computed? - В. М. Vladimirskiy (Высшее образование в России, 2022)
In this paper, a higher education institution ranking methodology based on the applicants’ Comprehensive State Examination (EGE) scores is proposed. This methodology is shown to be more correct than the existing one.